UJI AKTIVITAS ANTIPIRETIK SENYAWA MH2011 PADA TIKUS WISTAR JANTAN YANG DIINDUKSI BREWERâS YEAST - , ESTY OKTAVIARINI RIYANTI, Dr. Arief Nurrochmad, M.Sc., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
-